More 'Boundary of Gezer' Inscriptions: One New and Another Rediscovered - Mitchell, Eric; Dodd, R. Adam; Coyle, S. Cameron (2014)
The article discusses two 'Boundary of Gezer' inscriptions found in 2012. One inscription, classified as no. 4, had previously been discovered by Clermont-Ganneau but was never fully published, and had not been seen in the field since his time. The other is a newly discovered thirteenth Gezer boundary inscription; the tenth one with both תחמגזך and ΑΛΚΙΟΥ. In an appendix, the authors also attempt to sort out the disjointed nature of the discovery, publication and attribution of the 'Boundary of Gezer' inscriptions over time.